STUDY OF ENERGY EFFICIENCY OF CENTRAL PUMPING MAIN UNITS - Нагірний, Петро; Николин, Петро; Николин, Уляна (SWorldJournal, 2024)
The mathematical model of the centrifugal pump of main oil pipelines in relation to the display of mechanical losses was refined, energy indicators were determined according to its complex parameters, a vector diagram of the power of the pump unit was con